2010
DOI: 10.4028/www.scientific.net/ssp.168-169.341
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Magnetic Properties of Nickel Oxide Nanopowders

Abstract: Structure and magnetic properties of nickel oxide (NiO) nanopowders have been studied by X-ray/neutron diffraction, SQUID magnetometer, and micro-Raman spectroscopy. Our diffraction data indicate that at room temperature all NiO powders are antiferromagnetically ordered and have a rhombohedral (R-3m) phase. The SQUID magnetometry and Raman spectroscopy measurements support the presence of the antiferromagnetic ordering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 8 publications
(9 reference statements)
4
31
1
Order By: Relevance
“…Regarding the surface chemistry after the tribological experiments, all studied cases showed the presence of Ni oxide (NiO) [46,47]. This is straightforwardly detected with Raman spectroscopy by observing the resonance at 550 and 1100 cm −1 .…”
Section: Structural and Chemical Analysis Of The Wear Tracksmentioning
confidence: 65%
“…Regarding the surface chemistry after the tribological experiments, all studied cases showed the presence of Ni oxide (NiO) [46,47]. This is straightforwardly detected with Raman spectroscopy by observing the resonance at 550 and 1100 cm −1 .…”
Section: Structural and Chemical Analysis Of The Wear Tracksmentioning
confidence: 65%
“…The existence of AFM ordering at room temperature in NiO nanopowders with the crystallite sizes of 13-1500 nm has been recently confirmed in [6] by several experimental techniques, including neutron diffraction. It was also found that the crystal lattice of nanoparticles in AFM phase experiences weak rhombohedral distortion as in the bulk NiO [6].…”
Section: Introductionmentioning
confidence: 84%
“…Four NiO samples (S1, S2, S3, S4) were prepared according to the procedure described in [6]. The grain average sizes determined from the BET specific surface area measurements were 13 nm (S1), 100 nm (S2), 138 nm (S3) and 1500 nm (S4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the oxides, nickel oxide (NiO), an important p-typed semiconductor with stable band gap, has received much attention and been extensively studied and used frequently as electrode for lithium ion batteries and funnel cells [11,12], catalysts [13][14][15], electrochemical supercapacitors [16,17], dyesensitized photocathodes [18], magnetic materials [19,20], etc. However, with fast advancements in all areas of industry and technology, the pure NiO nanomaterials do not meet with the increasingly expanding commands.…”
Section: Introductionmentioning
confidence: 99%